Reconstructed chitosan with alkylamine for enhanced gene delivery by promoting endosomal escape. (1st January 2020) - Huang, Guojun; Chen, Qi; Wu, Wangteng; Wang, Jianwei; Chu, Paul K.; Bai, Hongzhen; Tang, Guping
Graphical abstract: Highlights: Chitosan was reconstructed with alkylamines for introducing multiple amino groups. Multiple amino groups with rational ratios functionally enhanced the buffering capacity of DMAPAPA-CS. DMAPAPA-CS can mediate endosomal escape by buffering the endo-lysosomal pH. DMAPAPA-CS showed a higher tissue permeability in tumor tissue, and DMAPAPA-CS/p53 significantly enhanced therapeutic effects on A549 tumor. Abstract: Poor buffering capacity of chitosan (CS) results in insufficient intracellular gene release which poses the major barrier in gene delivery. Herein, we reconstructed pristine CS with propylamine (PA), (diethylamino) propylamine (DEAPA), and N, N -dimethyl- dipropylenetriamine (DMAMAPA) to obtain a series of alkylamine-chitosan (AA-CS). The introduction of multiple amino groups with rational ratios functionally enhance the buffering capacity of AA-CS, among which DMAPAPA-CS showed buffering capacity of 1.58 times that of chitosan. The reconstructed AA-CS functionally enhance the ability of gene binding and endosomal escape. It was observed that the DMAPAPA-CS/pDNA complexes exhibit a notable gene delivery efficiency, which promotes the functionalization of loaded pDNA. Importantly, the in vivo delivery assay reveals that the deep penetration issue can be resolved using DMAPAPA-CS gene delivery vector. Finally, the DMAPAPA-CS is applied to deliver the therapeutic p53 gene in A549 bearing mice, showing efficient therapeutic potential for cancer.